Perancangan Kampanye Sosial Mengatasi Penyakit Maag - Novianti, Nurul Afifah; Tarmawan, Irwan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
Ulcer is a disease that attacks stomach acid. This disease is caused by sores or inflammation in the stomach that appears in the form of pain in the pit of the stomach, nausea, feeling full quickly in the stomach. The reason is because of uplexus. hy eating schedules and irregular lifestyle. Many people underestimate this disease. So it becomes a common thing even though it really can't be underestimated. But many people who do not know that stress is the cause of stomach acid rising into the throat. Even complaints of this disease caused by anxiety or stress factors that reach 70-80%. There are still many people who underestimate this ulcer disease. This is because the habits of unhealthy lifestyles and active generations are more susceptible to heartburn. From the conclusions above will be carried out the design of social campaigns, in this design aims to minimize ulcer disease, especially those that impact from stress.